PROBLEMS OF HIGHER SCHOOL IN THE ASPECT BOLOGNA PROCESS (Pedagogy of Higher and Secondary Education, 2004)
The advantages and disadvantages o f higher education modernization in accordance with Boulogne agreement areconsidered in the article; the problem o f higher pedagogical school o f Ukraine are concretized.